Income Levels And Inequality in Metropolitan Areas A Comparative Approach in OECD Countries - Boulant, Justine (OECD Regional Development Working Papers, 2016)
This paper assesses levels and distribution of household disposable income in OECD metropolitan areas. All indicators were produced through a dedicated data collection, which, for most countries, uses administrative data from tax records available at detailed local scale (i.e. municipalities, local authorities, counties, etc.). Using different estimation techniques, we provide internationally comparable figures for 216 OECD metropolitan areas. The results highlight stark differences in both income levels and inequality within metropolitan areas, even for those belonging to the same country. Larger metropolitan areas feature, on average, higher levels of household disposable income but also higher income inequality. The paper then provides a measure of spatial segregation, or the extent to which households with similar incomes concentrate within a metropolitan area. On the governance side, the paper finds a stable and positive relationship between administratively fragmented metropolitan areas and spatial segregation by income